Nursing Students' Interpretation of their Profession through their Internship in the COVID-19 Pandemic: A Phenomenological Study - Hediye Utli and Ahmet Butun (Professor Despina Sapountzi-Krepia, 2024)
Nursing Students' Interpretation of their Profession through their Internship in the COVID-19 Pandemic: A Phenomenological Study